A 24 HR global campaign to assess precision timing of the millisecond pulsar J1713+0747 - Dolch, T.; Lam, M.; Cordes, J.; Chatterjee, S.; Bassa, C.; Bhattacharyya, B.; Champion, D.; Cognard, I.; Crowter, K.; Demorest, P.; Hessels, J.; Janssen, G.; et al. (2014)
The radio millisecond pulsar J1713+0747 is regarded as one of the highest-precision clocks in the sky and is regularly timed for the purpose of detecting gravitational waves. The International Pulsar Timing Array Collaboration undertook a 24 hr global observation of PSR J1713+0747 in an effort to better quantify sources of timing noise in this pulsar, particularly on intermediate (1–24 hr) timescales. We observed the pulsar continuously over 24 hr with the Arecibo, Effelsberg, GMRT, Green Bank, LOFAR, Lovell, Nançay, Parkes, and WSRT radio telescopes. The combined pulse times-of-arrival presented here provide an estimate of what sources of timing noise, excluding DM variations, would be present as compared to an idealized √ N improvement in timing precision, where N is the number of pulses analyzed. In the case of this particular pulsar, we find that intrinsic pulse phase jitter dominates arrival time precision when the signal-to-noise ratio of single pulses exceeds unity, as measured using the eight telescopes that observed at L band / 1.4 GHz. We present first results of specific phenomena probed on the unusually long timescale (for a single continuous observing session) of tens of hours, in particular interstellar scintillation, and discuss the degree to which scintillation and profile evolution affect precision timing. This paper presents the data set as a basis for future, deeper studies.